Beeld en Evenbeeld : een Leidse parade. - Berk, Anne; Bolten-Rempt, Jetteke; Rijsdam, Jan; Roepers, Nicole; Wintgens Hötte, Doris; Wolthoorn, Rob; van Dommele, Marloes; van Iterson, Mia; Stedelijk Museum De Lakenhal, Leiden (Leiden : Stedelijk museum De Lakenhal, 2002)
Baauw, Inge ; Bauer, Renata ; Beierle, Norman ; de Berg, Fleur van ; Beumer, Astrid ; Braspenning, Maurice ; de Bruijn, Hans ; De Fundatie ; Dijkman, Annelies ; Drenth, Bernadette ; Duivenvoorden, Peter ; Fakkel, Arjenne ; Francken, Hanneke ; Geerts, Ben ; Geraedts, Pieter ; Goddijn, Annie ; de Haan, Marc ; Hakkaart ; van Hoogenhuyze, Michael ; van Houwelingen, Aad ; Kamphuis, Ernst ; Kattenberg, Peter ; Keijser, Hester ; Kleingeld, Jan ; Klijn, Trees ; Lakke, Allart ; Lamboo, Wim ; van Nieuwenborg, Frans ; Nijenhuis, Herby ; Overtoom, Willem ; Pol, Jan Van der ; Schilstra, Onno ; Schouten, Rob ; Sjardijn, Cock ; Snijder, Els ; Söll, Burkhardt ; van Tol, Christiaan ; Turk, Jacques ; Verhoef, Marijke ; van der Vlist, Annemarie ; Voeten, Teun ; de Water, Koos van ; de Wit, Frans ; Zelfde, Rob Van 't
biog, tent., bibliog. p. 126-133
Engels
Nederlands
Beeld en Evenbeeld, Stedelijk museum De Lakenhal Leiden, 22.03 - 15.09.2002
boek
Keywords: Leiden